Decomposition of natural catastrophe risks: Insurability using parametric CAT bonds - Morteza Tavanaie Marvi; Daniël Linders (Risks, 2021)
Nat Cat risks are not insurable by traditional insurance mainly because of producing highly correlated losses. The source of such correlation among buildings of a region subject to a natural hazard is discussed. A decomposition method is proposed to split Nat Cat risk into idiosyncratic (and hence insurable) risk and systematic risk (carrying the correlated part). It is explained that the systematic risk can be transferred to capital markets using a set of parametric CAT bonds. Premium calculation is presented for insuring the decomposed risk. Portfolio risk-return trade-off measures for investing on the parametric CAT bond are derived. Multi-regional and multi-hazard parametric CAT bonds are introduced to reduce the risk of the investment. The methodology is applied on a region with about 3000 residential buildings subject to flood hazards.
Keywords: 330; Nat Cat risk; insurability; CAT bond; risk decomposition; parametric bond; correlated risk; systematic risk; catastrophe risk management